Long‐term changes in spatial distribution of birds responding to a group‐selection timber harvest - Steven P. Campbell; Jack W. Witham; Malcolm L. Hunter Jr. (Wildlife Society Bulletin)
Abstract We investigated the spatial response of 20 bird species to a group‐selection timber harvest within a 40‐ha forest stand over a 20‐year period (5 yr preharvest and 15 yr postharvest). To characterize the spatial response of each species, we examined trends in 3 metrics: proportion of harvest‐created canopy‐gap area that occurred within the area used by a species in each year, average distance to the nearest gap of all observations of a species in a year, and distribution of distances between observations and gaps for each species in each year. Eight species (eastern wood‐pewee [Contopus virens], winter wren [Troglodytes troglodytes], hermit thrush [Catharus guttatus], Nashville warbler [Vermivora ruficapilla], black‐and‐white warbler [Mniotilta varia], pine warbler [Dendroica pinus], common yellowthroat [Geothlypis trichas], and white‐throated sparrow [Zonotrichia albicollis]) responded positively to the timber harvest (i.e., the proportion of gaps in their area of use increased, the distance from gaps decreased, and their use of gaps and edges [0–25 m from gaps] increased). In contrast, veeries (Catharus fuscescens), black‐throated green warblers (Dendroica virens), and ovenbirds (Seiurus aurocapillus) avoided gaps and edges. Changes in spatial distributions were generally short‐lived; by 15 years postharvest the use of the harvested areas by nearly all species had approached preharvest levels. The spatial response of birds to group‐selection timber harvesting indicates that there are unlikely to be serious long‐term effects of the harvest on forest bird populations. However, there may be more subtle, short‐term effects, such as crowding of mature‐forest bird species into surrounding forest, which merit further study. © 2012 The Wildlife Society.